KESETARAAN HAK DAN KEWAJIBAN SUAMI ISTRI DALAM PERNIKAHAN PERSPEKTIF AL-QUR’AN - Fuad, Zahri (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2023)
The Qur'an emphatically states that the equality of rights and obligations of husband and wife in the Qur'an is an equal partnership relationship between men and women with their role as servants of Allah, in order to realize a harmonious life to achieve sakinah mawaddah and mercy in their family life. The results of this study show that accusations of misogynistic or patriarchal Islam are wrong. Islam as a religion that upholds the values of justice and equality contains principles of equality such as husband and wife as servants of Allah, as caliphs on earth, and they both have the potential to achieve optimal performance. This will create feelings of love and affection between husband and wife. Another interesting thing that was found in this study is in the view of the Koran, each of the feminine and masculine characters in humans. What has been an academic debate about equality for husbands and wives in marriage so that it has an impact on social roles